2017
DOI: 10.1021/acs.jproteome.7b00005
|View full text |Cite
|
Sign up to set email alerts
|

HILAQ: A Novel Strategy for Newly Synthesized Protein Quantification

Abstract: Here we describe a new strategy, HILAQ (Heavy Isotope Labeled Azidohomoalanine Quantification), to rapidly quantify the molecular vulnerability profile to oxytosis, which is an oxidative stress-induced programed cell death pathway that has been reported to be involved in aging and neurodegenerative diseases. HILAQ was able to quantify 1,962 Newly Synthesized Proteins (NSPs) after 1h pulse labeling in HEK293T cell line, while 353 proteins were quantified using the previously published QuaNCAT protocol. HILAQ wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…The azide functional group on Aha enables selective enrichment through click chemistry-mediated solid-phase capture of Aha-labeled proteins. Combining BONCAT with pSILAC (e.g., BONLAC [ Bowling et al., 2016 ]/QuanCAT [ Howden et al., 2013 ] and HILAQ [ Ma et al., 2017 ]) improves the sensitivity and coverage of pSILAC and provides a quantitative comparison of protein synthesis rates across two conditions ( Eichelbaum et al., 2012 ). Using multiple MS analysis, this combined approach has been used for temporal analysis of newly synthesized proteins following macrophage activation ( Eichelbaum and Krijgsveld, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The azide functional group on Aha enables selective enrichment through click chemistry-mediated solid-phase capture of Aha-labeled proteins. Combining BONCAT with pSILAC (e.g., BONLAC [ Bowling et al., 2016 ]/QuanCAT [ Howden et al., 2013 ] and HILAQ [ Ma et al., 2017 ]) improves the sensitivity and coverage of pSILAC and provides a quantitative comparison of protein synthesis rates across two conditions ( Eichelbaum et al., 2012 ). Using multiple MS analysis, this combined approach has been used for temporal analysis of newly synthesized proteins following macrophage activation ( Eichelbaum and Krijgsveld, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“… 57 , 58 More recently, another method termed Heavy Isotope Labeled Azidohomoalanine Quantification (HILAQ) has been developed, in which light and heavy isotope labeled Aha variants are utilized for both tagging and quantification of nascent proteins. 59 As opposed to BONCAT and QuaNCAT, in which Click dependent biotin labeling and enrichment is performed at the protein level, in HILAQ the pre-mixed heavy and light Aha pulse-labeled lysates are first trypsin digested, and Click dependent biotin labeling and enrichment is then performed at the peptide level. This allows specific enrichment of Aha containing peptides for mass spectrometry identification and quantification.…”
Section: Proteomics Based Analysis Of Translationmentioning
confidence: 99%
“…Thus, while HILAQ is truly quantitative like QuaNCAT, the use of isotope labeled Aha does away with the need for double SILAC-BONCAT labeling and greatly simplifies the experimental workflow. 59 …”
Section: Proteomics Based Analysis Of Translationmentioning
confidence: 99%
“…Upon incorporation of AHA into NSPs, a biotin-alkyne can be covalently linked to the NSPs incorporating AHA using azide-alkyne click-chemistry 25 . Typically, enrichment has been performed on the protein level prior to digestion, but it has been reported that peptide enrichment significantly increased the number of NSPs identified 26 . In the improved protocol, trypsin digestion was performed on samples immediately after Trichloroacetic acid (TCA) precipitation, followed by peptide enrichment using biotin-streptavidin, a powerful tool which is widely used in biotechnology.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in 2016 it was reported that isobaric labeling (iTRAQ) and AHA were combined to enrich and quantitate NSPs 18 . In the past decade, MS-based AHA strategies have been successfully applied in multiple biological model organisms including Escherichia coli 36, 37 , C.elegans 24 , tadpoles 38 , mammalian cell line 26 , primary cells 13 , mouse 6 and Arabidopsis thaliana 16 .…”
Section: Introductionmentioning
confidence: 99%